Advanced Financial Accounting: An IAS and IFRS Approach - TAN, Pearl Hock Neo (Institutional Knowledge at Singapore Management University, 2008)
The book provides in-depth examples and explanations to accompany an advanced level financial accounting course. It is also among the first to feature detailed examples of the new Business Combinations standard.